Facultatively Anaerobic Staphylococci Enable Anaerobic Cutibacterium Species to Grow and Form Biofilms Under Aerobic Conditions - Jeffrey B. Kaplan; Michael Assa; Noor Mruwat; Miloslav Sailer; Suresh Regmi; Khalaf Kridin (Microorganisms)
Facultatively anaerobic Staphylococcus spp. and anaerobic Cutibacterium spp. are among the most prominent bacteria on human skin. Although skin microbes generally grow as multispecies biofilms, few studies have investigated the interaction between staphylococci and Cutibacterium spp. in dual-species biofilms. Here, we measured the mono- and dual-species biofilm formation of four staphylococcal species (S. epidermidis, S. hominis, S. capitis, and S. aureus) and two Cutibacterium spp. (C. acnes and C. avidum) cultured in vitro under both aerobic and anaerobic conditions. The biofilms were quantitated by rinsing them to remove planktonic cells, detaching the biofilm bacteria via sonication, and enumerating the cells by dilution plating. When cultured alone, staphylococci formed biofilms under both aerobic and anaerobic conditions, whereas Cutibacterium spp. formed biofilms only under anaerobic conditions. In co-culture, staphylococcal biofilm formation was unaffected by the presence of Cutibacterium spp., regardless of oxygen availability. However, Cutibacterium spp. biofilm formation was significantly enhanced in the presence of staphylococci, enabling robust growth under both anaerobic and aerobic conditions. Fluorescence confocal microscopy of the aerobic dual-species biofilms suggested that staphylococci create anaerobic niches at the base of the biofilm where C. acnes can grow. These findings demonstrate that staphylococci facilitate the colonization of Cutibacterium spp. in oxygen-rich environments, potentially explaining their presence in high numbers on the oxygen-exposed stratum corneum.